2018
DOI: 10.1111/scd.12342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary acetylcholinesterase and pseudocholinesterase in patients with Alzheimer's disease: A case–control study

Abstract: Aim:The aim of this study was to evaluate acetylcholinesterase (AChE) and pseudocholinesterase (PChE) in whole saliva in patients with Alzheimer's disease (AD) and in healthy subjects. Saliva has a high potential for keeping track of general health and diseases. AD is a type of dementia with reduction in brain cholinergic markers that causes memory, thinking, and behavior problems. Up to 90% decrease in AChE activity has been observed in AD. Methods and results:Thirty healthy subjects and 30 patients with AD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…The ratio of p-tau/total tau also increases in the case of AD [ 136 ]. The activity of lactoferrin and acetylcholinesterase was also assessed in AD patients [ 137 , 138 ].…”
Section: Exosomal Biomarkers and Their Role In Neurodegenerative Dmentioning
confidence: 99%
“…The ratio of p-tau/total tau also increases in the case of AD [ 136 ]. The activity of lactoferrin and acetylcholinesterase was also assessed in AD patients [ 137 , 138 ].…”
Section: Exosomal Biomarkers and Their Role In Neurodegenerative Dmentioning
confidence: 99%
“…The possible explanation for the lack of significant change of AChE might occur partly because the change of saliva AChE does not represent the changes of AChE and the cholinergic system in the target tissue due to the weak correlation of AChE in saliva and AChE in other tissues such as erythrocytes [ 30 ]. However, the recent study has reported that saliva AChE can be used as potential biomarkers to indicate the significant impairment of the cholinergic system and memory impairment in patients with Alzheimer's disease [ 31 ]. Therefore, the lack of significant change in saliva AChE might occur partly because cholinergic system change may not play a crucial role in the memory-enhancing effect induced by a single dose of mulberry milk.…”
Section: Discussionmentioning
confidence: 99%
“…One study searched DJ-1 proteins in Parkinson's patients (not statistically significant association) (18). The other one analyzed salivary metabolites in patient with Alzheimer's disease and found a statistically significant association between disease and biomarkers (19). Details on such papers are reported in Table 6.…”
Section: Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%